Legitimate lies: The relationship between omission, commission, and cheating. (10th February 2016) - Pittarello, Andrea; Rubaltelli, Enrico; Motro, Daphna
Abstract: Across four experiments, we show that when people can serve their self‐interest, they are more likely to refrain from reporting the truth (lie of omission) than actively lie (lie of commission). We developed a novel online "Heads or Tails" task in which participants can lie to win a monetary prize. During the task, they are informed that the software is not always accurate, and it might provide incorrect feedback about their outcome. In Experiment 1, those in the omission condition received incorrect feedback informing them that they had won the game. Participants in commission condition were correctly informed that they had lost. Results indicated that when asked to report any errors in the detection of their payoff, participants in the omission condition cheated significantly more than those in the commission condition. Experiment 2 showed that this pattern of results is robust even when controlling for the perceived probability of the software error. Experiments 3 and 4 suggest that receiving incorrect feedback makes individuals feel more legitimate in withholding the truth, which, in turn, increases cheating.